Review of Rebecca Beasley, Theorists of modernist poetry: T.S. Eliot, T.E. Hulme, Ezra Pound - Monk, Craig (My University, 2009)
This slim volume in the “Routledge Critical Thinkers” series concentrates not on one figure but on three. Students of modernism are less likely to discover much new about T.S. Eliot and Ezra Pound as they are to be reminded of the enduring relevance of T.E. Hulme, whose thought here is properly contextualized amongst that of his more prolific contemporaries. In Theorists of Modernist Poetry, Rebecca Beasley argues not just that the theoretical writings of these three modernists framed the most important cultural questions of the twentieth century, but that Hulme’s thought in its first decade was essential to the imagist movement and, hence, to the poetic development of Eliot and Pound themselves. As a result, the core of this book is organized around a half-dozen questions that trace disparate threads of the modern movement, each ending with a summary useful for classroom discussion.
Keywords: modernist poetry